Socialne inovacije kot nov tip kolektivnega delovanja - Hlebec, Valentina (Teorija in praksa, 2021)
Social innovation (SI) is a new social phenomenon characterised by an effort to better address a social need and also introduce new relationships between actors. This article explores two theoretical frameworks that may assist in understanding SI. We argue how, according to the structuration theory, SI may be conceptualised as a form of collective agency while, in the complexity theory, SI is seen as a form of self-organisation. Further, we find that in harmony with both theories two mechanisms are critically important for a SI to emerge, endure and, as we argue, to overcome the risks and impediments specific to SI. The first mechanism is collective learning and knowledge sharing, significant for sustaining the cohesiveness of actors as they confront the new and the unknown. The second is decentralised leadership, with specific competencies needed to bridge the differences between actors in their knowledge, modes of operation, and organisational cultures. These mechanisms are demonstrated in two cases of SI "community of practice" and "living labs", together with the considerable role of the public sector in sustaining them.
Keywords: collective agency; complexity theory; decentralised leadership; decentralizirano vodenje; Inovacije; Inovation; kolektivno delovanje; samoorganizacija; self-organisation; social innovations; socialne inovacije; structuration theory; strukturacijska teorija; teorija kompleksnosti